2021
DOI: 10.1101/2021.07.12.452122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A phage parasite deploys a nicking nuclease effector to inhibit replication of its viral host

Abstract: PLEs are phage parasites integrated into the chromosome of epidemic Vibrio cholerae. In response to infection by its viral host ICP1, PLE excises, replicates and hijacks ICP1 structural components for transduction. Through an unknown mechanism PLE prevents ICP1 from transitioning to rolling circle replication (RCR), a prerequisite for efficient packaging of the viral genome. Here, we characterize a PLE-encoded nuclease, NixI, that blocks phage development likely by nicking ICP1s genome as it transitions to RCR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Following, the observation that systems' distribution is contrasted, we set out to understand drivers of such heterogeneity. Several systems recently described (n=17), were discovered in prophages or their parasites 10,12,14,30,31 . These observations could suggest that systems encoded on prophages differ than those encoded in the chromosome.…”
Section: Families Of Anti-phage Systems Have a Heterogeneous Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following, the observation that systems' distribution is contrasted, we set out to understand drivers of such heterogeneity. Several systems recently described (n=17), were discovered in prophages or their parasites 10,12,14,30,31 . These observations could suggest that systems encoded on prophages differ than those encoded in the chromosome.…”
Section: Families Of Anti-phage Systems Have a Heterogeneous Distributionmentioning
confidence: 99%
“…A majority of these systems were uncovered through the "defense islands" method, using a guilt by association approach [1][2][3][4][5][6][7][8] . Others were discovered individually [9][10][11] or by looking into hotspots encoded in mobile genetic element [12][13][14] . It is thus now recognized that prokaryotic immunity is much more complex than previously perceived with evidence for intracellular signaling regulating defense 5,15 , chemical defense 7,16 , nucleotide depletion 8 , RNA mutations 4 , guardian systems 6 and the discovery of many prokaryotic defense systems which mechanisms are still unknown 1,4,12 The discovery of a stockpile of novel anti-phage systems questions our view of how prokaryotes defend themselves against viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the newly discovered PLE variants, however, only appeared for a short time, such as PLE6 which was detected once in Bangladesh in 1987, and PLE8 in Vietnam in 1995. We also detected one possible phage satellite with partial genetic relationship to PLEs, as has been described in non-cholera Vibrios recently (LeGault et al, 2021a), however its sequence could not be fully resolved from available data. It is highly likely that we still have not captured the full extent of PLE diversity and variant flux over time as V. cholerae isolate sampling was sporadic and limited until recent decades (with over half of all isolates collected in only the last nine years).…”
Section: Ples Have Evolved and Diversified Both Globally And Temporallymentioning
confidence: 71%
“…Annotation and sequence comparison of open reading frames confirmed that the newly detected PLEs 6-10 possess genes key to PLE function that have been characterized in the previously studied PLEs 1-5. These include nixI, which encodes a nickase that interferes with ICP1's ability to replicate and a supplementary gene stiX which increases NixI activity (LeGault et al, 2021a), lidI, which can accelerate lysis of the V. cholerae host cell (Hays and Seed, 2020), and capR, which acts to repress ICP1's capsid morphogenesis operon (Netter et al, 2021). The conservation of these genes indicates that the newly identified PLEs play similar roles as PLEs 1-5 as parasites of ICP1.…”
Section: Ples Have Evolved and Diversified Both Globally And Temporallymentioning
confidence: 99%